When water conservation matters: Examining how water scarcity experiences create windows of opportunity for effective water-saving policy initiatives. Issue 137 (November 2022) - Liu, Li-Yin; Brough, Christopher B.; Wu, Wei-Ning
Abstract: With projected water scarcity, educating the public on household water-saving is essential for water sustainability. This study investigates how experiences of water scarcity, perceived severity of water shortages, and perception of water sustainability affect residential water conservation behavior in Oklahoma, and aims to strengthen the residential water conservation studies in the United States—an understudied topic—and provide evidence-based suggestions to enhance residential water sustainability education. Based on two Zero-Inflated Poisson regressions, the results reveal that those who have experienced drought and are worried about the sustainability of water resources in their community take more no-cost steps to reduce their household water waste. Only experiences of drought have a positive impact on the number of cost-incurring steps taken by households. Based on the result, state and local government's water-saving initiatives can be more effective if they utilize the drought experiences to attract the public's attention. Highlights: Zero-Inflated Poisson regressions were estimated to test the hypotheses. Cost is a burden for household water conservation. Experience of drought increases household water saving behavior. Household income is negatively associated with household water conservation. Optimism for water sustainability leads to low engagement for water conservation.